ANALISIS PENGARUH KARAKTERISTIK INDIVIDU, FASILITAS, SUPERVISI, DAN MOTIVASI TERHADAP KINERJA PETUGAS PELAKSANA PELAYANAN ROGRAM MTBS (MANAJEMEN TERPADU BALITA SAKIT) DI KABUPATEN BANYUMAS TAHUN 2010 - Purwanti, Sugi (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2011)
Integrated Management of Childhood Illness (MTBS) as one as way to reduce infant mortality rate and under-five children mortality rate has been implemented in district of banyumas. However, infant mortality rate and under-five children mortality rate in 2007 was still high, 9.6/1000 live birth. The Objective of this study was to identify the influence of knowledge, work load perception on supervision and motivation towards the performance of MTBS program workers in the district of Banyumas. This was an observational-analytical study with a cross sectional approach. Structured questionnaire was used as study instrument. It had been tested for its validity and reliability. The numbers of samples used in this study was 99 respondents. Chi square and logistic regression test were implemented in the data analysis. Result  of this study showed that 51.5 % of respondents was in the age of 30-40 years old, 35.4 % of respondents was in the D3 midwifery level of educations, 73.3 % respondent’s job ocupation was civil servant. Among 39 primary health center (puskesmas), 15 of them had MTBS room. Respondents with poor knowledge were 56.7%. respondents with high motivation were 53.5%. Performence of MTBS service workers was sufficient (54.5%).Result of bivariate analysis indicated taht work load perceptions (p:0.0001, Exp B:9.734), motivation (p:0.005,Exp B: 3.9860 towards the performance of workers. Health office needs to provide MTBS training, modify workers perceptions on work load, privide  MTBS module and to do continuing research on work load analysis.   Key words      : Knowledge, supervision perception, work load perception, performance of MTBS service workers Bibliography   : 54 (1989-2008)